PERANCANGAN SISTEM INFORMASI SURAT KETERANGAN PENDAMPING IJAZAH (SKPI) BERBASIS WEB PADA POLITEKNIK NEGERI SAMBAS - Renol Burjulius; Wirandi; Sonty Lena (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2021)
Job opportunities are currently wide open, but the competition to enter the world of work is getting tougher where each individual must have optimal work skills so that they can convince every agency or industry of their abilities. As for individuals from college graduates from both the academic, vocational and professional fields with the experience and expertise possessed by each college graduate so that they can convince every agency or industry to get a professional workforce. Certificate of Companion Diploma (SKPI) is an additional document that has information about the academic achievements or qualifications of a graduate degree stating work ability, mastery of knowledge, For this Information Systems Design method, the author uses the waterfall as a software development methodology and UML (Unified Modeling Language) as a visual modeling method for object-oriented system design tools. With the SKPI Information System Design at the Sambas State Polytechnic, it can make it easier for students to upload SKPI document data, validate student SKPI documents carried out by academic supervisors, and make it easier for administration to obtain SKPI document data that has been uploaded and process SKPI.